Orthodontıc Brackets (A Literature Review) - Selim Arıcı (Galenos Yayinevi, 1998)
Throughout this century, one of the main trends of progress in the science of dental materials has been the improvement of both the function and aesthetic of orthodontic appliances. For this reason, many types of orthodontic brackets have been designed and manufactured from different materials. All these brackets have some advantages and disadvantages for orthodontic applications. Therefore a clinician should know the mechanical, chemical and clinical properties of the brackets in order to get best performance out of them.